Fast operando spectroscopy tracking in situ generation of rich defects in silver nanocrystals for highly selective electrochemical CO2 reduction - Xinhao Wu (Nature Portfolio, 2021)
Efficient electrocatalysts are crucial to the electrochemical carbon dioxide reduction. Here, the authors use the fast operando technique to explore a silver-based catalyst with improved catalytic performance benefiting from the suitable defect structures.